2005
DOI: 10.1292/jvms.67.611
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Rhodococcus equi in Mongolian Horses

Abstract: ABSTRACT. In native Mongolian horses, the incidence and distribution of Rhodococcus equi are poorly understood. One hundred and fourteen equine fecal samples and 71 soil samples were collected from the camp sites of 26 nomadic families located in three areas less than 100 km from Ulaanbaatar, Mongolia. Five fecal samples were also collected from foals of Przewalski's Horses introduced into the Hustai National Park, Mongolia. No R. equi was isolated from the Mongolian horses or the soil samples. However, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
2
Order By: Relevance
“…Moreover, the isolation rates and the mean number of R. equi from Tongliao City were significantly greater than those from the grasslands of Inner Mongolia. These data contrast with those of our recent study in which R. equi was absent from Mongolian horses in Ulaanbaatar, Mongolia [15].…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, the isolation rates and the mean number of R. equi from Tongliao City were significantly greater than those from the grasslands of Inner Mongolia. These data contrast with those of our recent study in which R. equi was absent from Mongolian horses in Ulaanbaatar, Mongolia [15].…”
contrasting
confidence: 99%
“…Our recent study showed no evidence of R. equi in either fecal samples of Mongolian foals or soil samples collected from the environments in which they were held by 26 nomad families in Ulaanbaatar. Avirulent R. equi were isolated only from the feces of descendants of introduced Przewalski's Horses at Hustai National Park [15]. In the present study, we were able to isolate R. equi from soil environment of horses at the Hulun Beier and Xilin Goler grasslands of Inner Mongolia, but no virulent R. equi were found in those isolates.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…Results of studies undertaken with strains isolated in Japan and Korea suggest their common origin [ 21 ]. According to Takai et al [ 32 ] one of the possible explanation may be a historical introduction of both type strains into these countries through Mongolian horses. However, there are no data at the moment about plasmid profiles of R .…”
Section: Discussionmentioning
confidence: 99%